Evaluation of Housing Product Quality Using Six Sigma Approach - Wahyu, Febtian Yusvika; Adi, Trijoko Wahyu (IPTEK Journal of Proceedings Series, 2017)
The property industry in Indonesia is one of the areas that has been developing, such as housing. Quality management is very important to be applied in any housing development process. This study aimed to design an evaluation model of housing product quality and assess the quality of housing product in Malang City. By using purposive sampling, this research focused on 9 unit samples. Quality assessment used was standard quality measures, CONQUAS 21 and CIS: 7. The analytical method applied was Six-Sigma approach with DMAIC tools. Moreover, Pareto and Fishbone diagram had also been used as analytical tools. The result revealed that there was a low sigma level in housing product, the average was 2,18 sigma. The critical causes of this problems were unskilled labours, poor materials, and climate changes. The action plans for the improvement that could be implemented were a selection of qualified contractors, job skill training for labours, and a regular inspection according to standard.